Pharmaceutical clusters: economic analysis of development and project ensurance of the effectiveness of the cluster model - Halchynskyi, Maksym; Yukhymenko, Petro; Polusmiak, Yuliia (Management and Entrepreneurship: Trends of Development, 2025)
The article examines the economic aspects of the development of pharmaceutical clusters as a tool for enhancing the competitiveness of the pharmaceutical sector in the context of globalization and economic transformation. Based on scientific data, an analysis and generalization of theoretical approaches to the essence of the cluster model, its structural elements, economic potential, and innovation attractiveness is conducted. The economic benefits and related risks are compared in a structured manner, allowing the identification of the strengths and weaknesses of the cluster model. One of the approaches to structural reform of the sector is the cluster-based model of production organization, which has proven effective in many countries. The international experience of promoting clusterization is analyzed using examples from the USA, India, and EU countries, with a focus on identifying effective practices for the formation of pharmaceutical clusters that can be implemented in the national economic context. Practical recommendations for improving cluster policy in Ukraine are proposed, including the introduction of special programs and the creation of favorable conditions for international partnerships and scientific research collaborations. The results of research on the economic aspects of pharmaceutical cluster development are extremely important for ensuring economic stability, technological progress, and access to high-quality medical products in Ukraine. The findings should be taken into account when developing strategies for the pharmaceutical industry’s growth and enhancing its competitiveness. JEL Classification: L16, L65, O25, O31, R11, R58, F63